Psychometric properties for the malay version of the assessment of criteria for specific internet-use disorders among young adults in Malaysia - Siaw, Yan-Li; Chua, Kah-Heng; Ruckwongpatr, Kamolthip; Tung, Serene En Hui; Gan, Wan Ying; Poon, Wai Chuen; Nadhiroh, Siti Rahayu; Nurmala, Ira; Üztemur, Servet; Chen, I-Hua; Griffiths, Mark D.; Lin, Chung-Ying (Wolters Kluwer Medknow Publications, 2025)
Introduction: Problematic internet use (PIU) can present itself in a variety of online activities. Given the increasing prevalence of PIU among young adults, there is a dearth of comprehensive assessment tools to characterize various PIU in Malaysia. The 11-item Assessment of Criteria for Specific Internet-use Disorders (ACSID-11) assesses specific PIU including online gaming, online buying-shopping, online pornography use, social networking use, and online gambling. The present study investigated the psychometric properties of the Malay ACSID-11. Methods: A cross-sectional study using an online survey was used for the data collection. The sample comprised 610 young adults aged 22.55 years (standard deviation ± 3.49). Participants were recruited from July 2023 to September 2023 using convenience sampling. Results: The confirmatory factor analysis findings supported the four-factor structure of the Malay ACSID-11 across gender, ethnicity, and academic achievement with good fit statistics: comparative fit index (CFI) ≥ 0.968, Tucker-Lewis index (TLI) ≥ 0.949, root mean square error of approximation (RMSEA) ≥ 0.057, standardized root mean square residual (SRMR) ≥ 0.028 (frequency response); CFI ≥ 0.968, TLI ≥ 0.958, RMSEA ≥ 0.079, SRMR ≥ 0.033 (intensity response). The different online subscales (except for some of the ACSID-11 online gambling subscales) showed good internal consistency (Cronbach's α and McDonald's ω between 0.58 and 0.90 for frequency responses; Cronbach's α and McDonald's ω between 0.61 and 0.93 for intensity responses). Conclusion: The Malay ACSID-11 is a valid and reliable instrument for assessing various specific PIU among Malaysian young adults. However, caution is required using the ACSID-11 to assess online gambling because some of its subscales had low internal consistency.